The Persistence of Tradition Amid Modernization: A Functionalist Study of Nubian Customs in Egypt - Wicaksono, Imam (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2024)
This study explores the customs and local traditions of the Nubian tribe in Egypt that have endured despite the pressures of modernization and globalization. The research addresses two key questions: the functions of the Nubian tribe’s customs and traditions that remain preserved today and the relationships between the various elements of Nubian customs. This study applies Bronislaw Malinowski’s functionalism theory, which asserts that each cultural element functions to fulfill human physiological and psychological needs. Additionally, Talcott Parsons’ Social System theory is used to understand how Nubian customs function as an integrated system in which roles and norms establish social order within the community. The findings reveal that enduring Nubian traditions include pregnancy rituals, traditional healing, the prohibition of women riding donkeys, marriage customs, pregnancy invocation rituals, death rites, and crocodile keeping. The holistic relationship among cultural elements is evident in the use of the Nubian language in rituals, oral traditions, and intergenerational communication, which serves to protect Nubian cultural identity from external cultural influences.